High porosity and light weight graphene foam heat sink and phase change material container for thermal management. (23rd July 2020) - Zehri, Abdelhafid; Samani, Majid Kabiri; Latorre, Martí Gutierrez; Nylander, Andreas; Nilsson, Torbjörn; Fu, Yifeng; Wang, Nan; Ye, Lilei; Liu, Johan
Abstract: During the last decade, graphene foam emerged as a promising high porosity 3-dimensional (3D) structure for various applications. More specifically, it has attracted significant interest as a solution for thermal management in electronics. In this study, we investigate the possibility to use such porous materials as a heat sink and a container for a phase change material (PCM). Graphene foam (GF) was produced using chemical vapor deposition (CVD) process and attached to a thermal test chip using sintered silver nanoparticles (Ag NPs). The thermal conductivity of the graphene foam reached 1.3 W m −1 K −1, while the addition of Ag as a graphene foam silver composite (GF/Ag) enhanced further its effective thermal conductivity by 54%. Comparatively to nickel foam, GF and GF/Ag showed lower junction temperatures thanks to higher effective thermal conductivity and a better contact. A finite element model was developed to simulate the fluid flow through the foam structure model and showed a positive and a non-negligible contributions of the secondary microchannel within the graphene foam. A ratio of 15 times was found between the convective heat flux within the primary and secondary microchannel. Our paper successfully demonstrates the possibility of using such 3D porous material as a PCM container and heat sink and highlight the advantage of using the carbon-based high porosity material to take advantage of its additional secondary porosity.